Public Sector Strategy Set Up - Ion POPA; Cosmin DOBRIN; Alina PROFIROIU; Ion VERBONCU (Transylvanian Review of Administrative Sciences, 2009)
In order to be realistic, a strategy must bescientifically based. This requires the considerationof two main factors: strategy premises andmodalities of strategy substantiation. The mainpremises of a strategic model are: to consider thelife cycle phase of the organization, to considerthe stakeholders, to assure the continuation of thestrategic model elaboration and implementation,systemic approach of strategy elaborationand implementation, economic activitiesinternationalization, international managerial knowhowtransfer. The following can be mentioned asmodalities of strategy substantiation: diagnosisstudies, forecast studies, market studies.